PLA2G6 Silencing Suppresses Melanoma Progression and Affects Ferroptosis Revealed by Quantitative Proteomics - Wang, Yifei; Song, Hao; Miao, Qiuju; Wang, Yan; Qi, Jinliang; Xu, Xiulian; Sun, Jianfang (Frontiers in Oncology, 2022)
Although phospholipase A2 group VI (PLA2G6) is involved in oncogenesis in several human tumors, its expression and role in cutaneous malignant melanoma (CMM) pathogenesis remains unclear. Here, by using the Oncomine and CCLE online database, immunohistochemistry, RT-qPCR, and western blotting analysis, we revealed that PLA2G6 was markedly up-regulated in CMM tissues compared to nevus tissues, as well as remarkably increased in vitro in SK-MEL-28 and M14 melanoma cell lines compared to human melanocytes. In vivo, PLA2G6 was also elevated in nine melanoma tissues compared to adjacent tissues. To investigate the malignant behaviors of PLA2G6 in CMM, SK-MEL-28 and M14 cell lines with PLA2G6 stable knockdown by RNAi strategy were constructed. Through CCK8 and colony formation assays in vitro and xenograft tumor experiment in vivo, we found that knockdown of PLA2G6 dramatically inhibited cell proliferation. The results of scratch-wound and transwell assays suggested that the migration and invasion of melanoma cells were prominently suppressed after silencing PLA2G6. In addition, flow cytometry showed that the knockdown of PLA2G6 promoted the apoptosis rate of melanoma cells. To further explore the potential molecular mechanism, we used liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) proteomic and bioinformatics analysis. The GO and KEGG analysis suggested that the underlying mechanism of PLA2G6 in CMM might be associated with the ferroptosis pathway, and ferroptosis-related proteins were validated to be differentially expressed in PLA2G6 knockdown SK-MEL-28 and M14 cells. Together, these results suggested that PLA2G6 knockdown significantly inhibited cell proliferation, metastasis, and promoted apoptosis in melanoma. Our findings on the biological function of PLA2G6 and the underlying association between PLA2G6 and ferroptosis in melanoma may contribute to developing a potential therapeutic strategy for melanoma.